2010
DOI: 10.3324/haematol.2010.029520
|View full text |Cite
|
Sign up to set email alerts
|

   T-cell killing of primary follicular lymphoma cells is dramatically potentiated by GA101, a type II glycoengineered anti-CD20 monoclonal antibody

Abstract: BackgroundAnti-CD20 monoclonal antibodies are major therapeutic agents for patients with follicular lymphoma and work through complement-mediated cytotoxicity and antibody-dependent cellular cytotoxicity. Optimization of antibody-dependent cellular cytotoxicity, in particular by amplifying its effectors, could further increase the efficacy of anti-CD20 monoclonal antibodies. Design and MethodsWe investigated the cytotoxic activity of Vγ9Vδ2 T cells against follicular lymphoma cells and whether this killing cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…These CD16 high gd T cells have specific phenotypic features that distinguish them from the CD16 low subset: they constitutively express several natural killer receptors (NKG2A/CD94) and high amounts of perforin, but express low levels of chemokine receptors (CXCR3, CCR6) and IFN-g [46]. They specifically respond to activation via CD16 and their ability to perform ADCC against tumor cells has been proven in vitro with several therapeutic antitumor mAbs: rituximab [48][49][50], trastuzumab [49,50], alemtuzumab [49], ofatumumab [48] and GA101 [48]. Surprisingly, the level of tumor cell cytotoxicity obtained by gd T cells through CD16 stimulation with these therapeutic mAbs is sometimes higher than the cytotoxicity obtained through natural TCR stimulation alone [48,50].…”
Section: Immune Cells Are Important Mediators Of Antibodyinduced Cytomentioning
confidence: 98%
See 1 more Smart Citation
“…These CD16 high gd T cells have specific phenotypic features that distinguish them from the CD16 low subset: they constitutively express several natural killer receptors (NKG2A/CD94) and high amounts of perforin, but express low levels of chemokine receptors (CXCR3, CCR6) and IFN-g [46]. They specifically respond to activation via CD16 and their ability to perform ADCC against tumor cells has been proven in vitro with several therapeutic antitumor mAbs: rituximab [48][49][50], trastuzumab [49,50], alemtuzumab [49], ofatumumab [48] and GA101 [48]. Surprisingly, the level of tumor cell cytotoxicity obtained by gd T cells through CD16 stimulation with these therapeutic mAbs is sometimes higher than the cytotoxicity obtained through natural TCR stimulation alone [48,50].…”
Section: Immune Cells Are Important Mediators Of Antibodyinduced Cytomentioning
confidence: 98%
“…They specifically respond to activation via CD16 and their ability to perform ADCC against tumor cells has been proven in vitro with several therapeutic antitumor mAbs: rituximab [48][49][50], trastuzumab [49,50], alemtuzumab [49], ofatumumab [48] and GA101 [48]. Surprisingly, the level of tumor cell cytotoxicity obtained by gd T cells through CD16 stimulation with these therapeutic mAbs is sometimes higher than the cytotoxicity obtained through natural TCR stimulation alone [48,50]. One explanation for these results could be that CD16 high gd T cells have weaker responses to PAgs than the CD16 low subset [46].…”
Section: Immune Cells Are Important Mediators Of Antibodyinduced Cytomentioning
confidence: 99%
“…Recent date showed that these cells not only served as guards in the innate immune system but also acted as a bridge between innate and adaptive immune responses by performing multiple functions (Bonneville et al, 2010). γδ T cells also played a prominent role in innate defenses against tumor formation by directly recognizing molecules expressed on cancer cells without antigen processing and presentation (Braza et al, 2011). Liver, largely accepted as an immune organ, is one of the richest source of γδ T cells.…”
mentioning
confidence: 99%
“…CD16 high γδ T cells constitutively express several NK cell receptors including NKG2A–CD94 and express high amounts of perforin, but low levels of IFN-γ [36]. They specifically respond to activation via CD16 and are capable of lysing tumors following exposure to mAbs including RTX [3840], TRAST [39,40], alemtuzumab [39], ofatumumab [38] and GA101 [38], and may facilitate NK cell function [41]. The synergy between γδ T cells and NK cells relies on an interaction between the CD137 ligand and CD137; activated γ9γ2 T cells enhance antitumor cytotoxicity of NK cells through CD137 engagement [42].…”
Section: Increasing Target–mab–effector Bindingmentioning
confidence: 99%